Schaum’s outline of theory and problems of financial management - Shim, Jae K. (McGraw-Hill, 1999)
Designed for both undergraduate and graduate students, this popular study guide25,000 copies were bought of the first edition! covers everything from financial analysis and forecasting, planning and budgeting to leverage and capital structure, mergers and acquisitions and multinational business finance. This closest-thing-to-a-personal-tutor includes many problems with fully worked out solutions and a comprehensive exam. It's ideal for independent study, as preparation for CMA and CFA exams and for professional review.